A Comprehensive Review of VOCs as a Key Indicator in Food Authentication - Han Yang; Manxi Wu; Xinyu Shen; Yichen Lai; Dengliang Wang; Chao Ma; Xianming Ye; Cui Sun; Jinping Cao; Chongde Sun; Yu Zhang; Yue Wang (eFood)
ABSTRACT This article presents an in‐depth review of the role of volatile organic compounds (VOCs) in food authentication, an area of increasing importance due to the rising complexity of food fraud cases. The inherent and unique profiles of VOCs in different food products serve as chemical fingerprints, enabling the differentiation of authentic food products from fraudulent ones across various food categories such as dairy, fruits, vegetables, meat, seafood, beverages, and grains. The review begins with an overview of the chemical properties and characteristics of VOCs, emphasizing their diversity and significance in the sensory experience of food products. The article explores VOCs' application in food authentication, providing valuable information on origin, variety, quality, ripening stage, and potential adulterations. Advancements in detection and analytical techniques, such as gas chromatography‐mass spectrometry (GC‐MS), proton transfer reaction‐mass spectrometry (PTR‐MS), selected ion flow tube‐mass spectrometry (SIFT‐MS), electronic noses (E‐noses) etc., are discussed. The article also addresses the challenges and limitations in VOC‐based food authentication, including variability in VOCs profiles, technical limitations, and regulatory considerations. In conclusion, the review underscores the potential of VOCs as indicators in food integrity, predicting that continued technological advancements and interdisciplinary collaboration will enhance food safety, quality, and traceability.